Thermal safety of dendritic lithium against non-aqueous electrolyte in pouch-type lithium metal batteries - Jiang, Feng-Ni; Yang, Shi-Jie; Cheng, Xin-Bing; Shi, Peng; Ding, Jun-Fan; Chen, Xiang; Yuan, Hong; Liu, Lei; Huang, Jia-Qi; Zhang, Qiang (Journal of energy chemistry, 2022)
With the rise of the specific surface areas of Li deposits, the initial exothermic temperature between Li metal and electrolyte reduces gradually. The heat release of per gram Li increases firstly and then reduces in a working battery. [Display omitted] A quantitative relationship between safety issues and dendritic lithium (Li) has been rarely investigated yet. Herein the thermal stability of Li deposits with distinct surface area against non-aqueous electrolyte in pouch-type Li metal batteries is probed. The thermal runaway temperatures of Li metal batteries obtained by accelerating rate calorimeter are reduced from 211 °C for Li foil to 111 °C for cycled Li. The initial exothermic temperature is reduced from 194 °C for routine Li foil to 142 °C for 49.5 m2 g−1 dendrite. Li with different specific surface areas can regulate the reaction routes during the temperature range from 50 to 300 °C. The mass percent of Li foil and highly dendritic Li reacting with ethylene carbonate is higher than that of moderately dendritic Li. This contribution can strengthen the understanding of the thermal runaway mechanism and shed fresh light on the rational design of safe Li metal batteries.